Pseudomonas stutzeri and Kushneria marisflavi Alleviate Salinity Stress-Associated Damages in Barley, Lettuce, and Sunflower - Szymańska, Sonia; Lis, Marta Izabela; Piernik, Agnieszka; Hrynkiewicz, Katarzyna (Frontiers in Microbiology, 2022)
Soil salinity is one of the most important abiotic factors limiting plant productivity. The aim of this study was to determine the effect of selected halotolerant plant growth-promoting endophytes (PGPEs, Pseudomonas stutzeri ISE12 and Kushneria marisflavi CSE9) on the growth parameters of barley (Hordeum vulgare), lettuce (Lactuca sativa) and sunflower (Helianthus annuus) cultivated under salt stress conditions. A negative effect of salinity was observed on the growth parameters of all investigated plants, including germination percentage and index, root length, number of leaves, fresh and dry weight; however, differences in salt stress tolerance among the investigated crops were observed (H. annuus > H. vulgare > L. sativa). Our data showed that the most crucial traits affected by endophyte inoculation under salt stress were chlorophyll concentration, leaf development, water storage, root development, and biomass accumulation. Thus, the influence of endophytes was species specific. K. marisflavi CSE9 promoted the growth of all tested plant species and could be considered a universal PGPEs for many plant genotypes cultivated under saline conditions. P. stutzeri ISE12 stimulated growth and mitigated salinity stress only in the case of barley. Bioaugmentation of crops with halotolerant bacterial strains can alleviate salt stress and promote plant growth; however, the selection of compatible strains and the verification of universal plant stress indicators are the key factors.